Investigating Nutrient Limitation Role on Improvement of Growth and Poly(3-Hydroxybutyrate) Accumulation by Burkholderia sacchari LMG 19450 From Xylose as the Sole Carbon Source - Oliveira-Filho, Edmar R.; Silva, Jefferson G. P.; de Macedo, Matheus Arjona; Taciro, Marilda K.; Gomez, José Gregório C.; Silva, Luiziana F. (Frontiers in Bioengineering and Biotechnology, 2020)
Burkholderia sacchari LMG19450, a non-model organism and a promising microbial platform, was studied to determine nutrient limitation impact on poly(3-hydroxybutyrate) [P(3HB)] production and bacterial growth from xylose, a major hemicellulosic residue. Nitrogen and phosphorus limitations have been studied in a number of cases to enhance PHA accumulation, but not combining xylose and B. sacchari. Within this strategy, it was sought to understand how to control PHA production and even modulate monomer composition. Nitrogen-limited and phosphorus-limited fed-batch experiments in bioreactors were performed to evaluate each one’s influence on cell growth and poly(3-hydroxybutyrate) production. The mineral medium composition was defined based on yields calculated from typical results so that nitrogen was available during phosphorus limitation and residual phosphorus was available when limiting nitrogen. Sets of experiments were performed so as to promote cell growth in the first stage (supplied with initial xylose 15 g/L), followed by an accumulation phase, where N or P was the limiting nutrient when xylose was fed in pulses to avoid concentrations lower than 5 g/L. N-limited fed-batch specific cell growth (around 0.19 1/h) and substrate consumption (around 0.24 1/h) rates were higher when compared to phosphorus-limited ones. Xylose to PHA yield was similar in both conditions (0.37 gP(3HB)/gxyl). We also described pst gene cluster in B. sacchari, responsible for high-affinity phosphate uptake. Obtained phosphorus to biomass yields might evidence polyphosphate accumulation. Results were compared with studies with B. sacchari and other PHA-producing microorganisms. Since it is the first report of the mentioned kinetic parameters for LMG 19450 growing on xylose solely, our results open exciting perspectives to develop an efficient bioprocess strategy with increased P(3HB) production from xylose or xylose-rich substrates.